Estudos do acoplamento spin-fônon e da magnetização reversa em óxidos do tipo perovskita - Vieira, Paulo Victor Coutinho (2018)
The work was divided into two stages. In the first step was investigated the existence of spin-phonon coupling in the La1-xYxFeO3 compound. For this, La1-xYxFeO3 samples were prepared for x = 0.00, 0.20, 0.40, 0.50, 0.60, 0.80 and 1.00 by the combustion method. X-ray diffraction measurements together with the Rietveld refinement, showed that all the samples present a single phase with orthorhombic structure, was also checked a decrease in volume and the vibrational modes undergo a shift to high frequencies as the amount of Y increases. By varying the temperature in the Raman measurements anomalies were identified in the intensities of the vibrational modes before the magnetic transition temperatures. This fact was then associated with the spin-phonon coupling. In the second stage of this work was performed a reverse magnetization (MR) study on the compound LaFe0.5Cr0.5O3 pure and doped with Sr. It was verified in this work that the MR can be adjusted by doping with non-magnetic and non-isovalent ions, and by varying the heat treatment temperature to obtain the compound. For this, samples of La1-xSrxFe0.5Cr0.5O3 were produced for x = 0.00 0.10, 0.20 and 0.50 by the combustion method. X-ray diffraction measurements with the Rietveld method revealed that the samples had a single phase. Samples with x <0.20 have an orthorhombic structure and the sample with x = 0.50 has a rhombohedral structure. The insertion of Sr2+ into the La3+ site induces a decrease in the network parameters and unit cell volume. With the measurements of XPS it was possible to verify the valences of the elements that occupy the site B of the perovskite structure. These measurements revealed that iron has 2+, 3+ and 4+ valences. While chromium presents 6+ and possibly 3+ and 4+ valences, however, due to the proximity of Cr3+ and Cr4+ lines, it was not possible to distinguish and quantify the presence of each element. The effect of reverse magnetization was studied by means of magnetization measurements as a function of temperature. It was observed that the Sr insertion is responsible for lowering the temperature where the magnetization inversion occurs (compensation temperature). In addition, it was possible to conclude that MR stop existing in the samples of La1-xSrxFe0,5Cr0,5O3 in high concentration of Sr2+ (x = 0,50), when applied high external magnetic field (10000 Oe) and when heat treated at low temperature (1000º C) the cause in each one of factors is discussed on the basis of competitions in between networks iron, chromium and ions, Fe4+ and possibly the Cr4+ ions that act with paramagnetic ions in the system.